Knowledge, attitudes, and practices toward osteoporosis: a questionnaire survey - Xue, Min; Xia, Jiesheng; You, Xiaohui; Zhu, Xun; Zheng, Li; Wei, Qi; Zheng, Miao; Tao, Jialong; Shen, Yuntian; Zhou, Qi; Qian, Jiani; Chu, Minjie; et al. (Frontiers in Public Health, 2025)
BackgroundOsteoporosis is a prevalent yet often underdiagnosed condition that leads to significant morbidity and healthcare burdens. This study explores the knowledge, attitudes, and practices (KAP) of the community-dwelling adults concerning osteoporosis and its daily management.MethodsThe cross-sectional study was conducted from June 1, 2024 to February 1, 2025 at the Second Affiliated Hospital of Soochow University and included outpatients aged 18 years and older. Demographic data and KAP scores were collected, and differences across demographic groups were analyzed. Structural equation modeling examined the relationships and mediation effects among knowledge, attitudes, and practices.ResultsA total of 776 valid questionnaires were analyzed. Among the respondents, 458 (59.02%) were female, 376 (48.45%) had taken basic bone health supplements, and 100 (12.89%) had participated in osteoporosis education. The median age of the participants was 39 years (range: 18–76). The mean scores for knowledge, attitude, and practice were 14.66 ± 9.06 (possible range: 0–38), 43.41 ± 5.00 (possible range: 12–60), and 54.00 ± 13.66 (possible range: 17–85), respectively. Significant positive correlations were found between knowledge and attitude (r = 0.434, p < 0.001), knowledge and practice (r = 0.441, p < 0.001), and attitude and practice (r = 0.463, p < 0.001). Structural equation modeling (SEM) results indicated that knowledge directly influenced attitude (β = 0.491, p = 0.023) and practice (β = 0.297, p = 0.020), while attitude directly influenced practice (β = 0.401, p = 0.009). Knowledge also indirectly affected practice through attitude (β = 0.197, p = 0.012).ConclusionThe study sample demonstrated insufficient knowledge, positive attitudes, and suboptimal primary osteoporosis prevention practices. Results indicated that knowledge directly influenced attitude and practice, while attitude directly influenced practice. Targeted educational interventions are crucial to enhance osteoporosis awareness and promote evidence-based preventive behaviors, ultimately improving bone health and reducing the risk of osteoporosis-related complications.